Odpowiedź :
Odpowiedź:
Szczegółowe wyjaśnienie:
a) x²=49 /√
x = 7 v x = -7
b) 2x² = 100 /2
x² = 50 /√
x = √50 v x = -√50
c) 3x² - 5x = 0
x(3x - 5) = 0
x = 0 v 3x - 5 = 0
3x - 5 = 0
3x = 5
x = 5/3
x = 0 v x = 5/3
d) -x² + 3x + 4 = 0
Wzór na deltę
b²-4ac = 0
3² - 4*(-1)*4 = 9 +16 = 25 = 5²
x1 = (-3-5)/(2*(-1)) = -8/ (-2) = 4
x2 = (-3+5)/(2*(-1)) = 2 / (-2) = -1
Odpowiedź:
[tex]x^2=49\\\\x=\sqrt{49}\ \ \ \ \vee\ \ \ \ x=-\sqrt{49}\\\\x=7\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-7\\\\\\2x^2=100\ \ /:2\\\\x^2=50\\\\x=\sqrt{50}\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-\sqrt{50}\\\\x=\sqrt{25\cdot2}\ \ \ \ \ \ \vee\ \ \ \ x=-\sqrt{25\cdot2}\\\\x=5\sqrt{2}\ \ \ \ \ \ \ \ \vee\ \ \ \ x=-5\sqrt{2}[/tex]
[tex]3x^2-5x=0\\\\x(3x-5)=0\\\\x=0\ \ \ \ \vee\ \ \ \ 3x-5=0\\\\x=0\ \ \ \ \vee\ \ \ \ 3x=5\ \ /:3\\\\x=0\ \ \ \ \vee\ \ \ \ x=\frac{5}{3}\\\\\\-x^2+3x+4=0\ \ /\cdot(-1)\\\\x^2-3x-4=0\\\\a=1\ \ ,\ \ b=-3\ \ ,\ \ c=-4\\\\\Delta=b^2-4ac\\\\\Delta=(-3)^2-4\cdot1\cdot(-4)=9+16=25\\\\\sqrt{\Delta}=\sqrt{25}=5\\\\x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-3)-5}{2\cdot1}=\frac{3-5}{2}=\frac{-2}{2}=-1\\\\x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-3)+5}{2\cdot1}=\frac{3+5}{2}=\frac{8}{2}=4[/tex]